Regeneration process of the karst water springs in Transdanubian Mountains, Hungary - Babák, Krisztina; Kiss, Ibolya; Kopecskó, Zsanett; Kovács, István Péter; Schweitzer, Ferenc (Hungarian Geographical Bulletin, 2013)
Since the 1940s and 50s, there have been several researches dealing with karst water springs and the mapping of the continuous karst water level of the Transdanubian Mountains. The karst water level sank because of the intense bauxite and coal mining between the 1950s and 1980s and it started to increase after the decrease of mining activity. However, only a few authors investigated and modelled the water level changes and the rejuvenation of karst springs in the karst reservoir. Our paper is about the mineral contents and geomorphic properties of karst water springs near a chosen reservoir and our aim was to get some information about the regeneration process of the karst water reservoir. The geomorphic properties of karst water springs were mapped, using detailed field survey (DGPS) and geomorphic mapping. The mineral contents of spring waters were analysed to prove their origin. GIS results show that the karst water level in the karst reservoir reached 180–190 m a.s.l.